A kinematic analysis of temporal differentiation of the four-way coronal stop contrast in Wubuy (Australia) - Bundgaard-Nielsen, R.; Kroos, Christian; Harvey, M.; Best, C.; Baker, B.; Goldstein, L. (Australasian Speech Science and Technology Association (ASSTA), 2010)
Coronal stop contrast series are rare in the world’s languages, and are often reported to be articulatorily, perceptually, andphonologically fragile, in particular in an /iCi/ context. We present electromagnetic articulometry (EMA) data on the temporal differentiation of the four-way coronal stop series in the Australian Aboriginal language of Wubuy. The results show that the articulation of the stop series (at least for the laminal versus apical distinction) is temporally differentiated. Importantly, the EMA data also show that the reportedly ‘fragile’ alveolar-retroflex contrast is temporally distinct, even in the context of high-front vowel /i/. The latter finding suggests that the articulation of the Wubuy retroflex is not incompatible with /i/, as has previously been proposed, though it may indeed be more effortful to achieve than in other vowel contexts.